Base Station Cooperation for Confidential Broadcasting in Multi-Cell Networks - He, Biao; Yang, Nan; Zhou, Xiangyun; Yuan, Jinhong (IEEE transactions on wireless communications, 2015)
We design linear precoders that perform confidential broadcasting in multi-cell networks for two different forms of base station (BS) cooperation, namely, multi-cell processing (MCP) and coordinated beamforming (CBf). We consider a two-cell network where each cell consists of an N-antenna BS and K single-antenna users. For such a network, we design a linear precoder based on the regularized channel inversion (RCI) for the MCP and a linear precoder based on the generalized RCI for the CBf. For each form of BS cooperation, we derive new channel-independent expressions to approximate the secrecy sum rate achieved by the precoder in the large system regime where K,N→∞ with a fixed ratio β=K/N. Using these results, we determine the optimal regularization parameters of the RCI and the generalized RCI precoders that maximize the secrecy sum rate for the MCP and the CBf, respectively. We further propose power-reduction strategies that significantly increase the secrecy sum rate at high transmit signal-to-noise ratios when the network load is high. Our numerical results substantiate the derived expressions, verify the optimality of the determined optimal regularization parameters, and demonstrate the performance improvement offered by the proposed power-reduction strategies.